الاستجواب البرلماني في دستور جمهورية العراق لعام 2005 : دراسة تحليلية - د. عامر عياش عبد بشير; أديب محمد جاسم (PROSPECTIVE RESEARCHES, 2023)
Interrogation is considered the most important tool used by parliament to implement its scrutiny mission on the governments' task. Since it conveys the meaning of accusation and accountability, it may lead to discredit the whole government or one of its members when its deviant is proved, which is known as ministerial responsibility. This study sheds light on this topic considering parliamentary questioning as an effective tool of inspection and overseeing on the performance of ruling ministers' attraction their attention when they are unconscious or deter them when they violate laws. Ultimately, interrogation is not more than effective way with its origins, rules and justifications, which strengthen the parliamentary system.